A review on strategy and organization characterization total quality management - Badri, Sireesha; G, Swetha; R, Nagalakshmi; K, Yasodha; R, Thriveni Bai (International Journal of Current Innovations in Advanced Research, 2024)
TQM is a recent advancement in management, where every activity is focused on enhancing customer satisfaction through ongoing process improvements.Research in TQM has evolved from the practical needs of organizations adopting this philosophy, with much of the literature being conceptual and geared toward practitioners. TQM is a business management strategy focused on enhancing the quality of an organization’s products and services through continuous improvement. Top of FormBottom of FormThere is a deficiency of a solid theoretical framework that categorizes past efforts and directs future research. To address this gap, a study of the existing TQM literature has been conducted. A comprehensive review, classification, and analysis of TQM research over the past two decades is provided. Additionally, it offers future research directions and serves as a valuable reference for the TQM literature. The proposed research suggestions aim to guide future advancements in the TQM field and contribute to its development into a formal discipline.